INTERPRETATION OF WOMEN’S LOVE IN AUTOBIOGRAPHY: EXPRESSION OF EMOTIONAL FREEDOM IN ’RASIDI TICKET’ AND ’ANYA SE ANANYA’ - Veena Joshi; Chitlangia, Bhavana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this research, it will be analyzed through the autobiographies of Amrita Pritam and Prabha Khaitan how Indian women writers define their love as an ’independent entity’ by going beyond social conventions. In this, the personal, emotional, and existentialist aspect of love will be prominent. This research paper attempts to understand the emotional depths, struggles and expression of freedom of women’s love through the autobiographies of two powerful writers—Amrita Pritam and Prabha Khaitan—’Rasidi Ticket’ and ’Anya Se Ananya’. The basic objective of the research is to show how love becomes not just an emotional experience for a woman, but also a powerful medium of self-acceptance, social resistance and ideological consciousness. While Amrita Pritam’s love is spiritual and lives in memories, Prabha Khaitan’s love is realistic, full of struggle and is connected to the identity of existence. Through their respective experiences, both the writers connect love with a woman’s independent identity and self-realization, in which the expectation of social acceptance becomes secondary.